PEMBELAJARAN ZIKIR RATIB AL-HADDAD DALAM MENINGKATKAN NILAI-NILAI SPIRITUAL SISWA DI MI - Haiah , Ummi; Rahman, Fathor (FORPIM PTKIS ZONA TAPAL KUDA, 2024)
The formation and development of morals is currently something important to do. One of them is by instilling religious spiritual values, which basically function to maintain and control human morals. To protect its students from problems related to morals, MI Maqnaul Ulum Mojogemi continues to strive to develop and shape the morals of its students using various methods, one of which is by instilling religious spiritual values ​​through routine activities of remembrance of Ratib Al-Haddad. This research aims to describe learning the remembrance of ratib al-haddad in improving students' spiritual values ​​at MI Maqnaul Ulum Mojogemi. This research uses a qualitative approach. Data collection techniques use observation, interviews and documentation. Meanwhile, the data analysis technique uses data reduction, data display and data verification. The data validity technique uses triangulation of sources and techniques. The results are: (1) Religious spiritual values ​​that can be instilled through routine activities of remembrance of Ratib Al-Haddad include: the value of discipline, a sense of responsibility, the value of leadership, and istiqomah in worship. (2) the implementation of the routine Ratib Al-Hadad remembrance activities went as expected. (3) The impact of routine Ratib Al-Haddad remembrance activities is quite positive in shaping students' morals.